Differences in Help-Seeking Behavior in Adolescents with Anxiety Disorder During the COVID-19 Pandemic - Erlian Indah Mustikawati; Ernawaty Ernawaty (Media Kesehatan Masyarakat Indonesia, 2021)
Adolescents represent one of the vulnerable groups that could suffer from mental and psychosocial health during the COVID-19 pandemic. This study aims to analyze behavioral differences in adolescents who have experienced anxiety disorders during the COVID-19 pandemic. The study used a cross-sectional design on 122 adolescents in East Java during the pandemic. Data was collected through a questionnaire via Google Forms in May 2021. Data analysis in this study used the Mann–Whitney test on SPSS Statistics 26. The current study found that male respondents (80%) show a higher tendency to have anxiety disorders compared with female respondents (74%). Meanwhile, there was no difference in the help-seeking behavior based on the gender of adolescent respondents’ who experienced anxiety disorders during the COVID-19 pandemic (p=0.291). The current study also found that there is no difference in help-seeking behavior between adolescents who experience anxiety disorders or those who do not experience anxiety disorder (p=0.449). Most adolescents with anxiety disorders tend to discuss their issues with friends and family to relieve anxiety, whereas some do not seek help because they can cope with anxiety disorders on their own, they think they do not really need help, they feel that no one cares about their problems, and there is a lack of supporting health facilities in the youth environment. Teenagers in East Java are advised to consult their mental health problems with experts to find relevant solutions.